Systems Approach toward a Greener Eco-efficient Mineral Extraction and Sustainable Land Use Management in the Philippines - Michael Angelo B. Promentilla (AIDIC Servizi S.r.l., 2021)
As the world transition towards a low-carbon future through renewable energy, mining of minerals and metals to attain this goal is substantial. The Philippines will play an important role in such global economy as it is the world’s fifth most mineral-rich country. However, their exploitation has not been maximized to benefit society. Benefits from the mineral resources sector remain less than 2 % of the country’s GDP since 2006, and the mining and mineral processing, including abandoned or legacy mines, are perceived negatively by the public. In low- and middle-income countries with weak implementation of mining and environmental legislation, the mining industry still operates in a linear system which is considered unsustainable. The mining, mineral extraction and processing, and metal extraction are designed to maximize profits with little plan on how to effectively manage mine wastes, protect the environment, transform post-mining land for beneficial use and empower impacted communities. This paper, thus, proposes a systems approach toward greener eco-efficient mineral extraction and sustainable land use management (SAGES). This approach will facilitate a paradigm shift, which is necessary to manage the country’s mineral endowments sustainably without compromising future land use of mining areas while at the same time supporting the needs and aspirations of the impacted host communities. It envisions extending the usability of mining areas beyond the life of the mine and integrating circular economy principles in addressing holistically mine waste management problems. The multi-R framework, originally developed in waste management (Reduce, Reuse, Recycle) and extended to circular economy strategies, has potential applications in mine waste management in the Philippines. An illustrative case study is then presented that employs a multi-R framework to address the mine waste in an operating Ni-laterite mining site.